2014
DOI: 10.1186/1476-4598-13-200
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-29 negatively regulates EMT regulator N-myc interactor in breast cancer

Abstract: BackgroundN-Myc Interactor is an inducible protein whose expression is compromised in advanced stage breast cancer. Downregulation of NMI, a gatekeeper of epithelial phenotype, in breast tumors promotes mesenchymal, invasive and metastatic phenotype of the cancer cells. Thus the mechanisms that regulate expression of NMI are of potential interest for understanding the etiology of breast tumor progression and metastasis.MethodWeb based prediction algorithms were used to identify miRNAs that potentially target t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 52 publications
4
54
0
1
Order By: Relevance
“…35 Interestingly, miR29 reportedly has an EMT-promoting effect. 36 Reportedly, TGF-b can initiate and maintain the EMT in various biological and pathologic systems. 26,37 Moreover, the findings in those two studies showed that suppression of TGFb signaling promoted CST under an inflammatory microenvironment, and that MMP2 was activated in the benign tissues with intact TGF-b signaling.…”
Section: Discussionmentioning
confidence: 99%
“…35 Interestingly, miR29 reportedly has an EMT-promoting effect. 36 Reportedly, TGF-b can initiate and maintain the EMT in various biological and pathologic systems. 26,37 Moreover, the findings in those two studies showed that suppression of TGFb signaling promoted CST under an inflammatory microenvironment, and that MMP2 was activated in the benign tissues with intact TGF-b signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Forced overexpression of miR-29b and miR-29a promoted an epithelial-to-mesenchymal transition (EMT) in MCF-7 and T47D cells while miR-29a repression reduced invasiveness of MDA-MB-231 triple negative breast cancer (TNBC) cells [25]. However, other studies indicate that miR-29a and miR-29b act as oncosuppressors in breast cancer cells by repressing cell proliferation, differentiation, and metastasis [21, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that NMI was highly expressed in myeloid leukemias and pancreatic ductal adenocarcinomas [25, 38]. By contrast, it was reported recently that NMI retarded breast cancer growth [39] while loss of NMI promoted epithelial-mesenchymal transition of breast cancer [40, 41]. However, the function and prognostic significance of NMI in glioma have never been studied.…”
Section: Introductionmentioning
confidence: 99%